Hematological, clinical and epidemiological aspects of Hepatozoon canis infection by parasitological detection in dogs from the rural area of Sousa, Paraíba, Brazil - Leonardo Vinícius Silva de Oliveira; Radabley Rith Almeida de Oliveira; Émerson Timóteo de Alcântara; Felipe Boniedj Ventura Álvares; Thais Ferreira Feitosa; Arthur Willian de Lima Brasil; Vinícius Longo Ribeiro Vilela (Ciência Rural)
ABSTRACT: Hepatozoonosis is caused by protozoa of the genus Hepatozoon. In dogs, the infection is caused mainly by Hepatozoon canis, and there are a few descriptions of the prevalence of this infection in the Northeast region of Brazil, especially in the semi-arid region. Therefore, we aimed to determine the prevalence of Hepatozoon canis infection in dogs in the rural area of Sousa, Paraíba, Brazil, as well as to determine the possible clinical and epidemiological aspects of this infection. Ninety-eight dogs in the rural zone of the municipality of Sousa that were at least 4 months old were evaluated, regardless of their breed or gender. Clinical examinations were carried out, and samples of systemic and peripheral blood were collected to determine the presence of the parasite in blood smears and carry out hemograms. In addition, epidemiological questionnaires about animal health and food management were completed. The prevalence of H. canis infections in dogs was 8.1% (8/98). There were three main changes in the hematological status: thrombocytopenia, anemia and hyperproteinemia, mainly related to percentage of leukocyte infection ≥5%, and also to the presence of clinical signs such as mucopurulent secretion, lymphadenomegaly, dry skin, pale mucous membranes, and lean or cachectic body score.